Microstructure and in-vitro test bioactivity behavior of Co-Cr-Mo (F-75)/hydroxyapatite in phosphate buffered saline solution - Shamsul Baharin, Jamaludin, Prof. Dr. (Technical University of Košice, 2014)
Link to publisher's homepage at http://www.qip-journal.eu